2009
DOI: 10.1073/pnas.0813307106
|View full text |Cite
|
Sign up to set email alerts
|

Membrane depolarization causes a direct activation of G protein-coupled receptors leading to local Ca 2+ release in smooth muscle

Abstract: Membrane depolarization activates voltage-dependent Ca 2+ channels (VDCCs) inducing Ca 2+ release via ryanodine receptors (RyRs), which is obligatory for skeletal and cardiac muscle contraction and other physiological responses. However, depolarization-induced Ca 2+ release and its functional importance as well as underlying signaling mechanisms in smooth muscle cells (SMCs) are largely unknown. Here we report that membrane depolarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
92
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 32 publications
(28 reference statements)
3
92
0
1
Order By: Relevance
“…However, the frequency of Ca 2ϩ sparks in RyR3 Ϫ/Ϫ cerebral artery myocytes is not significantly increased. Furthermore, we have shown that resting and depolarization-induced Ca 2ϩ sparks are not prevented in RyR3 Ϫ/Ϫ ASMCs (25) and that the downregulation of local Ca 2ϩ signaling by PKC⑀ is not blocked in RyR3 Ϫ/Ϫ cells either (24). These findings, taken together, clearly point out that CaN regulates local Ca 2ϩ signaling specifically through RyR1, but not RyR2 or RyR3.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…However, the frequency of Ca 2ϩ sparks in RyR3 Ϫ/Ϫ cerebral artery myocytes is not significantly increased. Furthermore, we have shown that resting and depolarization-induced Ca 2ϩ sparks are not prevented in RyR3 Ϫ/Ϫ ASMCs (25) and that the downregulation of local Ca 2ϩ signaling by PKC⑀ is not blocked in RyR3 Ϫ/Ϫ cells either (24). These findings, taken together, clearly point out that CaN regulates local Ca 2ϩ signaling specifically through RyR1, but not RyR2 or RyR3.…”
Section: Discussionsupporting
confidence: 57%
“…1E), unlike in cardiac myocytes where PP2A was shown to increase Ca 2ϩ sparks (40). RyRs are essential for spark formation; however, IP 3 Rs cross talk with RyRs, promoting Ca 2ϩ spark formation through a local CICR process (25,26). In the present study, we have revealed that CaN is able to modulate Ca 2ϩ sparks in the absence of functional IP 3 Rs (Fig.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations